Ride, Boldly Ride : the Evolution of the American Western. - Bandy, Mary Lea (University of California Press, 2012)
This comprehensive study of the Western covers its history from the early silent era to recent spins on the genre in films such as No Country for Old Men, There Will Be Blood, True Grit, and Cowboys & Aliens. While providing fresh perspectives on landmarks such as Stagecoach, Red River, The Searchers, The Man Who Shot Liberty Valance, and The Wild Bunch, the authors also pay tribute to many under-appreciated Westerns. Ride, Boldly Ride explores major phases of the Western's development, including silent era oaters, A-production classics of the 1930s and early 1940s, and the more psychologicall.